Perancangan Transmisi Listrik Wireless Menggunakan Dua Kumparan Metal - , SUPRIYADI; , Aris Budiman, S.T., M.T (2017)
The efficient electrical energy tranfer is important to day, so some people compete to develop new technologies that can transfer electrical energy without cable. Conventionally, the wire cable is the most efficient in this time. In this research, the writer creates a tool that can bring electrical energy through the air without cable. The magnetic flux phenomenon is a phenomenon that will be produced by the tool in this research. The existence of magnetic flux will cause resonance which will be ushered on the receiver side. The construction of the developed device is utilizing some copper windings. This copper coil is placed at the output of the transmitter side, and placed at the input of the receiver side. The input voltage of the transmitter is 19 volts DC and the current 4.74 Ampere. The coil used in the transmitter and the receiver has a 28.26 mm² cross-sectional area. In this research, the tool that has been created was tested by varying the load used on the receiver side and also the distance. The result of the conducted experiments, we get the best and worst efficiency. The best efficiency is 92.9 % with 25 watt of load at 2 cm of distance. And the power transfer is not happening with 25 watt of load at 10 cm of distance. From that experiments we can conclude that if the distance between transmitter and receiver is expanded, the less efficiency we get from the power transfer.